Insomnia as a presentation of hypertension in a 37-year-old male: A case report (Indian Journal of Case Reports, 2024)
This case report explores the rare presentation of insomnia as a symptom of hypertension in a 37-year-old male labor worker named Dinesh. Presenting with a 3-week history of insomnia, the patient’s diagnosis of hypertension highlights the importance of considering systemic conditions in patients with nonspecific symptoms like insomnia. The report delves into the interplay between hypertension and sleep disturbances, emphasizing the influence of lifestyle factors, particularly alcohol consumption, on blood pressure and sleep quality. The case underscores the necessity for clinicians to be aware of atypical presentations of common conditions like hypertension, which is often asymptomatic in its early stages but can manifest in varied and unexpected ways. Through this case, the report demonstrates the effectiveness of a comprehensive management approach, combining pharmacological treatment with lifestyle modifications, in improving both hypertension and related insomnia, thereby emphasizing the need for holistic patient care.